The influence of delirium on mortality and length of ICU stay and analysis of risk factors for delirium after liver transplantation - Ma, Ying; Li, Cuiying; Peng, Weiting; Wan, Qiquan (Frontiers in Neurology, 2023)
Objective: To analyze the incidence, timing, risk factors and prognosis of delirium after liver transplantation (LT). Methods: The clinical data of 321 patients undergoing LT in the Third Xiangya Hospital of Central South University from January 2018 to December 2022 were collected to investigate the incidence, onset, and risk factors for post-LT delirium and the impact of delirium on LT recipients' prognosis by statistical analysis. Results: The incidence of post-LT delirium was 19.3% (62/321), and the median interval between LT and onset of delirium was 20.1 hours. Univariate analysis showed that pre-LT variables (Model for End Stage Liver Disease (MELD) score, hospital stay, hepatic encephalopathy, infection, white blood cell (WBC) count, lymphocyte count, abnormal potassium, lactulose use) , intraoperative variables (red blood cell transfusion, remimazolam use, dexmedetomidine use) and post-LT variables (hypernatraemia, acute rejection, reoperation, basiliximab use, tacrolimus concentration) were associated with post-LT delirium. Multivariate logistic regression analysis revealed that MELD score at LT ≥22[OR=3.400, 95%CI:1.468-7.876, P=0.004], pre-LT hepatic encephalopathy[OR=3.224, 95%CI:1.664-6.244, P=0.001], infection within 2 months prior to LT[OR=2.238, 95%CI:1.151-4.351, P=0.018], acute rejection [OR=2.974, 95%CI:1.322-6.690, P=0.008], and reoperation [OR=11.919, 95%CI:2.938-48.350, P=0.001] were independent risk factors for post-LT delirium. Post-LT delirium was reduced in LT recipients exposing to intraoperative remimazolam[OR=0.287, 95%CI:0.113-0.733, P=0.009] or ≥25μg of intraoperative dexmedetomidine [OR=0.441, 95% CI 0.225-0.867, P= 0.018]. As for clinical outcomes, patients with delirium had a higher percentage of staying at the (ICU) ≥7 d after LT than those without delirium [OR=2.559, 95% CI 1.418-4.617, P= 0.002]. Conclusion: The incidence of delirium was high and the onset of delirium was early after LT. Risk factors for post-LT delirium included high MELD score at LT, pre-LT hepatic encephalopathy and infections, acute rejection and reoperation. Intraoperative use of remimazolam or dexmedetomidine reduced post-LT delirium. Delirium had a negative impact on the length of ICU stay.